Current and emerging new treatment strategies for mantle cell lymphoma. Issue 5 (May 2013) - Humala, Karem; Younes, Anas
Abstract Mantle cell lymphoma is a relatively rare type of non-Hodgkin lymphoma that accounts for approximately 6000 new cases per year in the USA. The median age of patients at presentation is around 65 years, and almost all patients present with stage IV disease. Over the past decade, our understanding of the molecular pathology of the disease has substantially improved. Furthermore, intensive chemotherapy treatment options were developed to improve the complete remission rates and to prolong the remission duration. More recently, several targeted agents have shown promising clinical results with good safety profiles. Future directions should focus on incorporating these novel agents in new less toxic regimens, and should also identify biomarkers that can better match patients with effective treatment strategies.